The Influence of Brand Image and Service Quality on Customer Satisfaction At Winaria Hotel 1 Siak Sri Indrapura City - Mandataris Mandataris; Rizma Sahzira (Publikasi Indonesia, 2024)
This study aims to determine the influence of brand image and service quality on customer satisfaction at Winaria 1 Kota Siak Sri Indrapura hotel. The method used in this study was descriptive and the sample in this study amounted to 96 respondents who were determined using Purposive Sampling and using questionnaires as data collection instruments. From data analysis which includes validity tests, reliability tests, linear regression analysis, hypothesis testing and determination coefficient tests, the results show that brand image has a significant effect on customer satisfaction, service quality has a significant effect on customer satisfaction and the results of brand image and service quality F tests on customer satisfaction, meaning that brand image and service quality simultaneously have a significant effect on customer satisfaction in hotel Winaria 1 Siak Sri Indrapura City.